The Role of Provinces, States, and Territories in Shaping Federal Policy for Indigenous Peoples' Health. Issue 2 (3rd April 2019) - Halabi, Sam
ABSTRACT: Under both Canadian and United States law, the availability and quality of healthcare and health services to Indigenous peoples are primarily a federal responsibility. Nevertheless, sub-national authorities—most importantly provinces, states, and territories—play a crucial role by virtue of covering (often through federal mandate) services, and regulating health facilities and health personnel off-reserv(ation). While both federal governments have undertaken efforts to transfer, within their fiduciary obligations, their responsibilities for Indigenous peoples' health to the management of Indigenous peoples themselves, that transfer has considered or included provincial, state, and territorial authorities and resources unevenly, and, in some cases, in tension with the objectives of respecting standards for quality and access. This article applies the methodology used by Canadian researchers of the sub-national health authority issue to the health transfer experience in the United States. The article summarizes findings that demonstrate similar deficiencies as those present in the Canadian transfer process. The article further outlines the experiences of Hawai`i and Ontario as offering models through which to address some of these deficiencies. The article finally suggests that there is a positive relationship between greater participatory models adopted by provinces, states, and territories and better health outcomes among Indigenous groups so included.